2000
DOI: 10.1560/c5y8-vf2c-61k9-t6yu
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion studies using contact mechanics

Abstract: We report adhesion studies using the JKR contact mechanics method and poly(dimethylsiloxane) (PDMS) cross‐linked networks. When such networks are extracted, interdigitation of tethered chains into extraction zones at the network‐network interface results in a significant enhancement of adhesion. When these networks come into contact with a silicon oxide surface, an increase in adhesion hysteresis is observed in the order of increasing molecular weight between crosslinks, with a scaling factor of 1/2. Subjectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…JKR measurements made using functionalized poly(dimethylsiloxane) (PDMS) lenses have been a powerful tool for fundamental adhesion studies, but JKR measurements using the SFA give more information, including force−distance profile and the shape of the surfaces in contact. Using the SFA, JKR-type measurements have been made between bare mica samples, , Langmuir−Blodgett monolayers, thin polymer films, and gold−thiol self-assembled monolayers, yielding values for surface energy that agree well with those obtained from wetting studies in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…JKR measurements made using functionalized poly(dimethylsiloxane) (PDMS) lenses have been a powerful tool for fundamental adhesion studies, but JKR measurements using the SFA give more information, including force−distance profile and the shape of the surfaces in contact. Using the SFA, JKR-type measurements have been made between bare mica samples, , Langmuir−Blodgett monolayers, thin polymer films, and gold−thiol self-assembled monolayers, yielding values for surface energy that agree well with those obtained from wetting studies in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…The large adhesion hysteresis observed for PDMS lenses in contact with oxide surfaces (such as SiO 2 and sapphire) has been reported previously in the literature. 43,44,56,57 Choi et al also showed that the W a during approach is not different for the adhesion of a PDMS lens to surfaces functionalized with selfassembled monolayers having varying concentrations of polar OH headgroups. 58 However, in their experiments, the adhesion hysteresis increased with an increase in concentration of surface OH groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, for SiO 2 /Si substrate, the W a calculated from pull-off is 360±5 mJ/m 2 (∼6 times the value obtained from loading) indicating a large adhesion hysteresis, consistent with literature. 43,44 Same is true for bare and graphene-coated sapphire, except for a slightly larger adhesion hysteresis for graphene-coated sapphire than graphene-coated SiO 2 /Si. The high adhesion hysteresis observed for bare substrates has been attributed to acid-base interactions between the acidic surface Si-OH (or Al-OH) groups of silicon wafer (or sapphire) and weakly basic siloxane (Si-O-Si) groups of PDMS.…”
Section: Adhesion Measurementsmentioning
confidence: 91%
See 2 more Smart Citations